Latest Trends in Lateral Flow Immunoassay (LFIA) Detection Labels and Conjugation Process - Mirica, Andreea-Cristina; Stan, Dana; Chelcea, Ioana-Cristina; Mihailescu, Carmen Marinela; Ofiteru, Augustin; Bocancia-Mateescu, Lorena-Andreea (Frontiers in Bioengineering and Biotechnology, 2022)
LFIA is one of the most successful analytical methods for various target molecules detection. As a recent example, LFIA tests have played an important role in mitigating the effects of the global pandemic with SARS-COV-2, due to their ability to rapidly detect infected individuals and stop further spreading of the virus. For this reason, researchers around the world have done tremendous efforts to improve their sensibility and specificity. The development of LFIA has many sensitive steps, but some of the most important ones are choosing the proper labeling probes, the functionalization method and the conjugation process. There are a series of labeling probes described in the specialized literature, such as gold nanoparticles (GNP), latex particles (LP), magnetic nanoparticles (MNP), quantum dots (QDs) and more recently carbon, silica and europium nanoparticles. The current review aims to present some of the most recent and promising methods for the functionalization of the labeling probes and the conjugation with biomolecules, such as antibodies and antigens. The last chapter is dedicated to a selection of conjugation protocols, applicable to various types of nanoparticles (GNPs, QDs, magnetic nanoparticles, carbon nanoparticles, silica and europium nanoparticles).